MINI-REVIEW: VARIASI AGEN DEPROTONASI DALAM SINTESIS ZIF-8 DAN APLIKASINYA - Fausiah, Ulfa; Syaima, Husna (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Mini-review this discusses recent studies related to the synthesis of ZIF-8 with variations of deprotonation agents and their applications. ZIF-8 with the molecular formula C8H12N4Zn is generally synthesized from Zn(NO3)2.6H2O (zinc nitrate hexahydrate) or other metal salts as a central metal source bonded to C4H6N2 (2-methylimidazole) as an organic compound and water as a solvent. In recent years, research on ZIF-8 has continued to grow with various modifications made by researchers. The synthesis process generally involves the use of expensive and flammable organic solvents in the synthesis medium and results in harmful effects to the environment due to its toxic nature. This raises urgency in ZIF-8 synthesis innovation, one of which is with a green synthesis method using water-based solvents. In the synthesis of ZIF-8, deprotonation agents such as NH4OH, TEA, NAOH and others are often used. The use of this deprotonation agent allows the formation of ZIF-8 with good crystal size, surface area, pore volume and % yield from ZIF-8 produced both synthetic ZIF-8 can be used in various fields such as antibiotic adsorption, catalysts, and separation. Keywords : synthesis, deprotonation, ZIF-8, antibiotic